2020
DOI: 10.1007/s11136-020-02716-x
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and overall survival: a prospective study in patients with head and neck cancer treated with radiotherapy

Abstract: Purpose We aimed to examine whether pre-treatment, post-treatment and change in health-related quality of Life (HRQoL) is associated with survival, in patients with head and neck cancer (HNC). Methods We included 948 newly diagnosed HNC patients treated with primary or adjuvant (chemo)radiotherapy with curative intent. The EORTC QLQ-C30 questionnaire was assessed pre-treatment and at 6 weeks, 6 months and 12 months post-treatment. Multivariable Cox regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 47 publications
(65 reference statements)
0
10
0
Order By: Relevance
“…Shortened operation time improves postoperative recovery and reduces further morbidity. Rehabilitation and reintegration into daily life are key as HRQOL is associated with overall survival in patients with HNC [ 23 , 24 ]. A higher HRQOL not only at diagnosis, but also post-treatment has been shown to result in improved survival rates [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shortened operation time improves postoperative recovery and reduces further morbidity. Rehabilitation and reintegration into daily life are key as HRQOL is associated with overall survival in patients with HNC [ 23 , 24 ]. A higher HRQOL not only at diagnosis, but also post-treatment has been shown to result in improved survival rates [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rehabilitation and reintegration into daily life are key as HRQOL is associated with overall survival in patients with HNC [ 23 , 24 ]. A higher HRQOL not only at diagnosis, but also post-treatment has been shown to result in improved survival rates [ 23 ]. Therefore, the choice of reconstructive method and the postoperative treatment may well be associated with oncological outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Though prospective data are lacking, recent retrospective studies have reported beneficial effects of EBRT on selected patients (20)(21)(22). Based on these results, EBRT after final incomplete resections of IR-DTC may offer locoregional control (LRC) and probably overall survival (OS), although radiation related morbidity after extensive repeated surgery will probably influence the quality of life (23). The aim of this study was to evaluate LRC and overall survival (OS) after postoperative EBRT for both microscopic and macroscopic non-radically resected locally advanced IR-DTC, and to assess potential side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Though prospective data are lacking, recent retrospective studies have reported beneficial effects of EBRT on selected patients ( 20 , 21 , 22 ). Based on these results, EBRT after final incomplete resections of IR-DTC may offer locoregional control (LRC) and probably overall survival (OS), although radiation-related morbidity after extensive repeated surgery will probably influence the quality of life ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…To put this in broader perspective, the improvement in survival may even in part relate to the increasing incidence of HPV-induced OPSCC and associated favorable prognosis [ 4 ]. Hence, the advances in clinical management apparently do not directly translate into survival benefits, although improved function and quality of life are reported and are important as well [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%